The right to effective jurisdictional guarantee and the application of atypical means of execution - Zimiani, Laís Silva (2021)
The Brazilian Civil Procedure Code provides in article 139, item IV, allowing the application of atypical executive measures in a subsidiary manner to typical executive methods. Atypical executive means are creative and powerful instruments that can cause substantial disruption to the executed, which is why they should be applied only when in line with the fundamental and sectoral principles of execution, as well as with national legislation and jurisprudence. The legal provision is indispensable for the granting of the fundamental right to effective judicial protection by the State-judge, but it cannot be applied in an indiscriminate and discretionary manner, considering that the atypical means of execution do not have the same guaranteed of predictability in the application of typical executive means. The research was carried out through the identification of concepts, norms and fundamental principles of law and was guided by the inductive method, with specific bibliographic review, as well as by the legislative and jurisprudential analysis on the theme.